Structural response of glass fiber reinforced polymer tubes infilled with lightweight aggregate concrete. (2022) - Bhuvaneshwari, P.; Aravind, S.R.; Shravan, Harish; Nigilesh Kanna, R.
Abstract: The purpose of the study is to reduce the self-weight of column using light weight aggregate concrete (LWC). The conventional coarse aggregate in concrete was replaced with Pumice aggregate to achieve LWC (R10, R20, R30, R40, R50). The reduction in density using LWC was noticed. To enhance the structural performance of LWC, cement was partially replaced with Ground Granulated Blast Furnace Slag (GGBFS) and Metakaolin (MK) mineral admixtures. LWC without and with mineral admixtures were cast as columns (UC-NMA, UC-MA). The effect of the confinement was noticed by casting similar mixes as infill in Glass Fiber Polymer Tubes (GFRP- C-NMA, C-MA). The axial load - displacement behaviour was compared for columns. Comparison of the results showed that confinement offered by GFRP tubes has highly enhanced the performance of infilled LWC. Parametric analysis shows that R30-MA was the optimum mix to be used as infill for GFRP tubes, to have enhanced structural performance along with reduced density.